PERAN AKUNTAN DATAM PENERAPAN GOOD CORPORATE GOVERNANCE - Paulina Permatasari (Center for Economic Studies Universitas Katolik Parahyangan, 2003)
Comprehensive Corporate Governance concept start growing since' The New York stock Exchange Grash 'on October 1987, where there were many multinational company rccorded in New York stock Exchange, had big financlal losses. At that time, for hidding the internal problem in their company, many excecutlves did ' window dressing ' and also , financial engineering'. Triggering wlth that event, many Good Corporate Govemance concept are developed. At the same time, Accountant are forced to accommodate excecutives in implementing GCG in their companies.